2021
DOI: 10.1136/bmjmilitary-2020-001721
|View full text |Cite
|
Sign up to set email alerts
|

Civil–military cooperation in the early response to the COVID-19 pandemic in six European countries

Abstract: BackgroundThe COVID-19 pandemic has presented many countries with significant health system and economic challenges. The role of civil–military cooperation in a health crisis of the magnitude presented by COVID-19 remains virtually unexplored. This review aims to detect and identify typologies, if any, of associations between security or military systems and the national response measures during the COVID-19, as adopted by six European countries during the early phase of the outbreak (January to March 2020).Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
2
14
0
1
Order By: Relevance
“…Among six European countries (UK, France, Spain, Italy, Belgium and Sweden), evaluated in a review for the civilmilitary cooperation in the early response to the COVID-19 pandemic, 'Deployment of military (field) hospitals to augment local capacity' returned the second most frequent elicitation. France returned the highest category elicitation (25 times), followed by Italy (9 times), Spain (5 times) and Sweden (1 time), whereas UK and Belgium did not elicit this category [32]. Moreover, Spain and Italy recorded the most frequent elicitations of the most frequent category elicited by the search results ('Allocation of military capability to national response') [32].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among six European countries (UK, France, Spain, Italy, Belgium and Sweden), evaluated in a review for the civilmilitary cooperation in the early response to the COVID-19 pandemic, 'Deployment of military (field) hospitals to augment local capacity' returned the second most frequent elicitation. France returned the highest category elicitation (25 times), followed by Italy (9 times), Spain (5 times) and Sweden (1 time), whereas UK and Belgium did not elicit this category [32]. Moreover, Spain and Italy recorded the most frequent elicitations of the most frequent category elicited by the search results ('Allocation of military capability to national response') [32].…”
Section: Discussionmentioning
confidence: 98%
“…France returned the highest category elicitation (25 times), followed by Italy (9 times), Spain (5 times) and Sweden (1 time), whereas UK and Belgium did not elicit this category [32]. Moreover, Spain and Italy recorded the most frequent elicitations of the most frequent category elicited by the search results ('Allocation of military capability to national response') [32]. In Italy on 1 March 2021, a General of the Army Corps was appointed Extraordinary Commissioner for the implementation and coordination of the containment and contrast measures of the epidemiological emergency COVID-19 and for the execution of the national vaccination campaign [33].…”
Section: Discussionmentioning
confidence: 99%
“…Upon reviewing the literature, it was found that the theoretical research on civilmilitary cooperation relations in COVID-19 emergency situations is still limited, despite existing studies that have reinforced the potential of the military and the importance of parallel health systems that seek to increase the capacity of the civil health system in times of emergency. An example is the remarkable article by Gad et al [4], who carried out a cross-sectional study in six European countries (i.e., United Kingdom, France, Spain, Italy, Belgium and Sweden), illustrating the impact of the military on the national responses of COVID-19, where, in some cases, there was extensive collaboration between the military and civilian health systems. In reality, the Armed Forces became involved in the response to COVID-19 for two reasons [3]: first, because the pandemic directly affected the Armed Forces' operational readiness and activities; second, because the Armed Forces had a political interest in engaging in the crisis response, showing taxpayers that they are efficient and important to society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The armed forces of most countries play an important role in national/local disasters and emergencies as well as in response to military threats. Countries across the globe have mobilized their armed forces in response to the COVID-19 pandemic, placing them at increased risk for viral exposure (1)(2)(3). COVID-19 outbreaks among military personnel highlight their susceptibility to SARS-CoV-2 infection and the importance of disease surveillance of this critical workforce (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%